ANALISIS KAPASITAS RUANG PARKIR SEPEDA MOTOR PADA SMA (SLUA) SARASWATI 1 DENPASAR - I Ketut Olgi Aditya Surya; I Gusti Agung Gde Suryadarmawan; Ni Ketut Sri Astati Sukawati (Jurnal Ilmiah Teknik Universitas Mahasaraswati Denpasar (JITUMAS), 2021)
Saraswati 1 Denpasar High School is one of the centers of educational activities located on Jl. Cambodia No.11 A, North Denpasar Subdistrict, which has developed both in terms of facilities and infrastructure as well as the number of students. This made the parking lot not functioning optimally because some students parked their vehicles out of place. Therefore, the purpose of this paper is to determine the capacity and characteristics of motorcycle parking at SMA (SLUA) Saraswati 1 Denpasar. The increase in the number of new students every year at SMA (SLUA) Saraswati 1 Denpasar will have a consequence of increasing vehicle ownership and can increase parking demand. Therefore, it is necessary to analyze the parking characteristics in the current conditions. And this problem needs to be solved through a field survey to find out exactly what problems exist. In solving these problems, this study aims to analyze the characteristics of parking, namely parking capacity, parking availability, and parking needs in the current state of the parking system and being able to plan parking patterns. with the availability of existing parking lots.